Analisis Semiotika Visual Pada Sampul Majalah Tempo Edisi “Noda Satu Putaran” - Damasemil, Calvin (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 1 (2024): ISU-ISU PEMBANGUNANDO - 10.24843/JIWSP.2024.v06.i01.p04, 2024)
The 2024 presidential election contest is deemed to have numerous violations and fraud. This has attracted the attention of the public and the mass media, especially Tempo Magazine. The magazine, known for its characteristic illustrated covers in every issue with various characters and visual styles that often become controversial, is the subject of this study. This research aims to uncover the meaning behind the cover of Tempo Magazine's February 18-25, 2024 edition titled "Stains of a Single Round." The study employs a qualitative approach with descriptive interpretive analysis. Data collection techniques in this research include observation and documentation. The method used is visual semiotics with Roland Barthes' semiotics model encompassing denotation, connotation, and myth. The results of this study identify that the fraud committed by Prabowo Subianto's camp can tarnish democracy and develop into an ideology in society, where everything can be done to achieve victory, including dishonest methods. The power obtained through such fraudulent processes can be perceived as something that everyone is entitled to without shame.